STUDI ETNOBOTANI TUMBUHAN PANGAN SUKU KAILI IJA DI DESA BORA KECAMATAN SIGI BIROMARU KABUPATEN SIGI SULAWESI TENGAH - Yulianti Rombe Payung; Miswan Miswan; Ramadhanil Pitopang (Biocelebes, 2016)
Etnobotanic study on “Food Plants” of Ija Kailinese in Bora village Sigi Biromaru district of Central Sulawesi was undertaken during period of March to April 2015. This study was aimed to abtain the plant species as “ food plants “ which parls were used as food, and how did Ija peoples procesed the plan as food. Qualitative and quantitative methods were used in this study, by interview technique with Open-ended questions on the questioner sheets, with 47 respondents. Based From the results, there were go plant sepecies covered of 34 families which were used as Food Plants by Ija peoples. The highest percentage of usefull parts were Fruits (42%). The Ija peoples were used and processed the plants as food by consumed them directly of processed by Boiled, grilled, steam, fried, and cooked with coconut milk. Ija peoples had used these plant species as traditional food (corn, kelor, and bavoa).   Key word : Society of Kaili Ija, Bora village, Sigi, Central Sulawesi, Etnobotani, Food Plant